A Gloss on the State Theory of Money: Simmel and Knapp - Waizbort, Leopoldo (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2020)
In his Staatliche Theorie des Geldes, published in 1905, Georg Friedrich Knapp presented the thesis that underlies so-called ‘chartalism’: “Das Geld ist ein Geschöpf der Rechtsordnung.” Formulated at a time when the basing of money on precious metal was considered indispensable (metalism), Knapp’s theory seeks an eminently social foundation of money, based on the legal order and the State. Knapp thus moved away from more substantialist conceptions of money; his theory is based on the practical functions and performances of money and points to the decisive problem of trust (in the acceptability and value of money). Although Georg Simmel, in his Philosophie des Geldes, published in 1900, did not develop a properly chartalist approach, he offers a number of points of support to the chartalist theory. The overcoming of the substantial character of money in favour of its functional character and his conception of money as relation, as well as the logical genesis of money and value as eminently social, offers a foundation to a social theory of money, of which the state theory of money suggested by Knapp would be a modalization.